2022
DOI: 10.3390/biomedicines10123184
|View full text |Cite
|
Sign up to set email alerts
|

AXL-Receptor Targeted 14FN3 Based Single Domain Proteins (Pronectins™) from 3 Synthetic Human Libraries as Components for Exploring Novel Bispecific Constructs against Solid Tumors

Abstract: A highly specific AXL-receptor targeted family of non-immunoglobulin, single domain protein binders (Pronectins™) have been isolated from three (3) synthetic libraries that employ the human scaffold of the 14th domain of Fibronectin III (14FN3) and evolutionary CDRs diversity of over 25 billion loop sequences. The three libraries, each containing diversity in two loops, were designed to expand upon a human database of more than 6000 natural scaffold sequences and approximately 3000 human loop sequences. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Consistently, here we demonstrated that pAXL×CD3ε indeed redirects T cells toward AXL-expressing sarcoma cells, leading to a dose-dependent T-cell activation, with a consequent release of inflammatory cytokines and cytolytic molecules. Our results are in accordance with data recently reported, showing that pAXL×CD3ε exhibits cytotoxic effects on AXL-positive MDA-MB-231 cells and minimal cytotoxicity on AXL-negative CHO cells [ 38 ]. Moreover, we found enhanced cytotoxic effects as a function of increased concentrations of pAXL×CD3ε, which was highly promising taking into account the presence of immune cells in the TME of sarcomas.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistently, here we demonstrated that pAXL×CD3ε indeed redirects T cells toward AXL-expressing sarcoma cells, leading to a dose-dependent T-cell activation, with a consequent release of inflammatory cytokines and cytolytic molecules. Our results are in accordance with data recently reported, showing that pAXL×CD3ε exhibits cytotoxic effects on AXL-positive MDA-MB-231 cells and minimal cytotoxicity on AXL-negative CHO cells [ 38 ]. Moreover, we found enhanced cytotoxic effects as a function of increased concentrations of pAXL×CD3ε, which was highly promising taking into account the presence of immune cells in the TME of sarcomas.…”
Section: Discussionsupporting
confidence: 93%
“…A highly specific anti-AXL Pronectin™, a non-immunoglobulin and single-domain protein, has been isolated from synthetic libraries based on the human scaffold of the 14th domain of fibronectin III (14FN3), as previously described [ 38 ]. By bioinformatic analysis aimed to select the best candidate within the amino acid loop diversity and minimize or prevent immunogenicity, 6 Pronectins™ with a KD < 10 nM were identified and AXL54 was chosen for targeting purposes (KD = 8 nM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation